(untitled) (Research, Society and Development, 2024)
In this study, we evaluated the early growth stages of maize plants cultivated in saline-sodic soil treated with various types of biochar. Biochar from sugarcane bagasse, orange bagasse, and corncobs was applied to a clayey saline-sodic soil and transferred to soil columns. After leaching, we measured the electrical conductivity (EC) and the exchangeable sodium percentage. Maize plants were grown in the leached soil. Plant biomass and nutrient concentration were determined. Biochar reduced EC to 3.20 dS m-1 and ESP to 2.56%. In the control soil, some seeds barely germinated without biochar, and plant growth was impaired. Conversely, all biochar treatments promoted seed germination and plant development. The CCB treatment not only enhanced plant growth but also achieved the best nutritional balance, as evidenced by plant nutrient concentration, which is similar to values typically found in maize plants during the early growth stages. However, the OBB treatment could not reduce the EC and ESP values to acceptable levels. These findings suggest that SCB and CCB biochar could be a promising solution for improving soil quality and promoting plant growth in salt-affected soils, thereby contributing to the field of sustainable agriculture.